Peran Otoritas Jasa Keuangan (OJK) dalam Mengawasi Fintech Lending sebagai Instrumen Ekonomi Digital - Gandasari, Nur Mutiara; Hidayat, Rendy Riansyah; Siswajanthy, Farahdinny (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
Fintech lending, as a form of digital economy, has changed the financial services landscape in Indonesia by providing more inclusive access to financing. However, the rapid growth of this sector also raises challenges, such as inadequate regulations, operational risks, and low consumer protection. The Financial Services Authority (OJK) has a central role in supervising and regulating this industry to ensure operations comply with laws and business ethics. This research aims to analyze the role, authority and effectiveness of OJK supervision of fintech lending, based on a normative juridical approach. Data was obtained through literature study and analysis of related documents. The research results show that even though the OJK has established various regulations, the effectiveness of supervision still faces obstacles, including the lack of transparency of fintech platforms and the challenges of continuously developing technology. This study provides strategic recommendations to strengthen supervision and create closer collaboration between regulators and industry players.